Результати констатувального етапу педагогічного експерименту формування базових професійних компетенцій бакалаврів з психології у процесі вивчення природничо-наукових дисциплін - Хавіна, Ірина Валер'ївна (My University, 2018)
У статті аналізується результати експериментального дослідження формування базових професійних компетенцій бакалаврів з психології у процесі вивчення природничо-наукових дисциплін. Описано етапи експериментального дослідження. Відповідно до критеріїв та показників виділені та охарактеризовані рівні сформованості базових професійних компетенцій бакалаврів з психології. Показано узагальнений результат рівня сформованості базових професійних компетенцій бакалаврів з психології на констатувальному етапі педагогічного експерименту.

The article analyzes the results of an experimental study of the formation of basic professional competences of bachelors from psychology in the process of studying natural sciences disciplines. The stages of experimental research are described. According to the criteria and indicators, the levels of formation of the basic professional competences of bachelors in psychology are identified and characterized. The generalized result of the level of formation of the basic professional competences of bachelors from psychology at the stage of the pedagogical experiment is shown.
Results of the constant stage of pedagogical experiment of formation of basic professional competencies of bacalaurs of psychology in the prcess of study of natural research disciplines
Keywords: навчальний процес; педагогічна діяльність; мотивація; комунікативність; pedagogical experiment; basic professional competencies; pedagogical technology; qualifying stage; bachelors on psychology